Intervensi gizi, sanitasi, dan kesehatan bagi anak jalanan melalui pelibatan partisipasi masyarakat - Irayana, Ika; Yarliani, Ikta (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2022)
Community involvement is key to improving the nutrition, sanitation, and health conditions of street children. This study examines the role of nutrition, sanitation, and health interventions involving community participation for street children. In the context of this research, a community-based participatory approach was used at Al-Ajyb Child Friendly School, Sudimampir Market, Banjarmasin City. This research explores the linkages between nutrition, sanitation, and health for street children and promotes the importance of early education and community involvement in meeting their needs. Community-Based Participatory Research was used in this study, involving various stakeholders. The findings of the study revealed various challenges faced by street children, such as nutrition, sanitation, and limited access to education and health services. Additionally, the study highlighted the important role of community-based interventions in promoting healthy behavior and raising awareness of the importance of nutrition and sanitation. Thus, collaboration between various parties is expected to translate the study findings into concrete actions aimed at improving the welfare of street children and enhancing their future prospects.